Control of Personal Data and Cyber ​​Space by Global Digital Platforms in Relation to Indonesia's Digital Sovereignty - Fauzi, Engrina; Citra, Helfira; Marwenny, Elwidarifa; Alfitrianti, Nia (Jurnal Ilmiah Ekotrans & Erudisi, 2024)
The dominance of foreign digital platforms in the application ecosystem within Indonesia poses significant implications for the sovereignty of the Indonesian state; the utilization of such foreign digital technologies results in the inadvertent surrender and delegation of citizen data to foreign entities for monitoring and processing purposes. This phenomenon has elicited concern among legal scholars, as the usage of foreign applications signifies the applicability of the legal frameworks from the countries of origin of these applications. This raises critical questions regarding the sovereignty of the Indonesian state, particularly concerning its ability to exert control over data and cyberspace in the context of global platforms. The methodological approach employed in this investigation is grounded in normative legal research, utilizing a conceptual framework that examines relevant legal statutes. The aggregation and distribution of personal data constitutes an infringement upon individual privacy rights, as the right to privacy inherently encompasses the prerogative to determine the provision of personal information. The strategic policies and initiatives undertaken by the Indonesian government to bolster national digital sovereignty can be realized through several measures: the implementation of comprehensive personal data protection standards to enhance national digital sovereignty, the establishment of an independent authority for personal data protection, the fortification of cybersecurity measures to mitigate data security risks, and the jurisdictional enforcement of cyberspace law towards achieving digital economic sovereignty. There exists a pressing need for extensive regulatory frameworks to safeguard personal data as an integral component of human rights. A balance must be struck in the management of personal data processing, ensuring the protection of rights and fostering awareness among data subjects, thereby facilitating the development of a secure digital economic ecosystem that offers legal certainty for enterprises and enhances consumer confidence. Furthermore, the establishment of equitable international personal data protection regulations is essential to support the advancement of the digital economy through arrangements governing cross-border data flow.